THE EFFECT OF FINANCIAL MONITORING INFORMATION SYSTEM (SIMONIKA) ON FINANCIAL REPORTING EFFICIENCY - Payuyu, Defriansyah; Monoarfa, Mohamad Agus Salim; Juanna , Andi (Universitas Ibn Khaldun Bogor, 2023)
The research aims to determine to what extent the effect of the financial monitoring information system or sistem informasi monitoring keuangan (abbreviated as si-monika) on the efficiency of financial statements at the General Election Commis-sion of Gorontako City. The data analysis technique employed simple linear regres-sion analysis with the sample of 37 respondents. At the same time, the method used in this research was a quantitative method. The finding revealed that the financial monitoring information system (simonika) had a positive and significant impact on the efficiency of financial statements at the General Election Commission of Goron-talo City. This indicated that the better the implementation of financial monitoring information system (simonika) would increase the efficiency of financial statements.